2020
DOI: 10.1002/ima.22423
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic mass segmentation using multichannel and multiscale fully convolutional networks

Abstract: Breast cancer is one of the leading causes of death among women worldwide. Mammographic mass segmentation is an important task in mammogram analysis. This process, however, poses a prominent challenge considering that masses can be obscured in images and appear with irregular shapes and low image contrast. In this study, a multichannel, multiscale fully convolutional network is proposed and evaluated for mass segmentation in mammograms. To reduce the impact of surrounding unrelated structures, preprocessed ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The proposed model also showed notable results to separate each BI-RADS breast density class where LIBRA failed. A multichannel and multiscale fully convolutional network for mammogram mass segmentation was proposed by Xu [117]. Preprocessing was carried out to reduce the influence of nearby structures that are negligible.…”
Section: Fcn For Mammogram Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model also showed notable results to separate each BI-RADS breast density class where LIBRA failed. A multichannel and multiscale fully convolutional network for mammogram mass segmentation was proposed by Xu [117]. Preprocessing was carried out to reduce the influence of nearby structures that are negligible.…”
Section: Fcn For Mammogram Segmentationmentioning
confidence: 99%
“…Conversely, Unet in calcification detection achieved only 70.3% sensitivity on DDSM. Among FCN-based methods, the technique of Xu et al [117] proved to have remarkably high inference knowledge capabilities scoring 0.91 dice similarity coefficient on two different datasets (DDSM, INBreast) in mass segmentation. Bhatti et al [127] showed reasonably accurate performances of the Mask RCNN-FPN method on DDSM and INBreast in detection and segmentation of breast lesions (91% accuracy).…”
Section: Pros and Cons Of Deep Learning Approachesmentioning
confidence: 99%
“…Among the abnormality types, masses are reportedly major contributors to breast cancer [16]. Therefore, in this paper, we aim to address the identification of masses that generally has two forms: mass detection [17][18][19][20] and mass segmentation [21][22][23][24][25]. Mass segmentation provides more comprehensive information, including border information; hence, in this paper, the main task is mass segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The preprocesses of feature selection and feature extraction are used to reduce the data dimensionality for overcoming this drawback. The deep CNN-based methods combine the multiconvolutional pooling layers (>10 layers in general configuration) and a classification layer to perform the automatic end-to-end enhancement process, noise filtering, feature extraction, and pattern recognition in this proposed topic, such as amass classification, lesion detection and localization, and lesion segmentation/ROI detection, by using fully convolutional network (FCN), Unet CNN, region-based CNN (R-CNN), faster R-CNN, TTCNN (transferable texture convolutional neural network), and Grad-CAM (gradient-weighted class activation mapping)-based CNN [31][32][33][34][35][36][37][38]. The multiconvolutional-pooling processes can extract the desired features from low-level features to high-level information (sharpening process) for detecting nor-mality objects, and then can increase the detection accuracy.…”
Section: Introductionmentioning
confidence: 99%